Executive Functions of Obsessive Compulsive Disorder and Panic Disorder Patients in Comparison to Healty Controls - TOPÇUOĞLU, VOLKAN (AVES, 2017)
Introduction: Patients with obsessive compulsive disorder (OCD) have impaired cognitive functions, including attention, verbal and visual memory, and visual-spatial abilities as well as executive function But some studies did not show any disturbance in executive function of patients with OCD. To date, only few studies have been conducted on neuropsychological functioning of patients with panic disorder (PD). There are limited studies to reach a definite conclusion on executive functions of patients with OCD and those with PD. In this study, we aimed to measure executive functions of patients with OCD and those with PD compared with those of healthy controls. Although there are many studies on cognitive functions of patients with OCD, there appears to be no consistency in results and no findings have been obtained to enable us to reach definite conclusions. Although there are very few studies on neuropsychological functions of patients with PD, impairments on a set of cognitive functions have been demonstrated. To date, no finding with respect to impairment in executive functions of patients with PD has been published. PD and OCD are disorders manifesting similar characteristics, with the presence of anxiety and avoidance behavior. Besides this, patients with OCD also have symptoms such as obsessions and compulsions that are characteristics of this disorder. We aim to compare executive functions in the three groups (patients with OCD, those with PD, and healthy controls) in this study. Method: Seventeen patients with OCD and 15 patients with PD who were diagnosed according to Diagnostic and Statistical Manual of Mental Disorder -IV-TR (DSM-IV-TR) and 26 healthy control subjects were included in this study. Patients who used medication as well as those with medical illnesses and Axis-I comorbidities were excluded. The healthy control group subjects were matched with the patients in terms of age, gender, and education. Structured Clinical Interview for DSM-IV Axis-I Disorders-Clinical Version (SCID-I), Hamilton Depression Rating Scale (HDRS), and Yale-Brown obsessive compulsive scale tests (Y-BOCS) were administered to the patients. Trail Making Tests (TMT), verbal fluency tests (Controlled Oral Word Association Test and Categorical Naming), Stroop Test, and Wisconsin Card Sorting Test (WCST) were administered to the study groups. Results: According to our results, there was no statistically significant difference between the three study groups with respect to executive functions. There was also no significant correlation between executive tests' results and Y-BOCS'in the OCD group. Conclusion: The results of the PD group are in line with that reported in literature. The results of the OCD group can be explained by a lack of medication usage and any comorbidity including depression. A small sample size is the major limitation of our study.
Keywords: Obsessive compulsive disorder; panic disorder; executive function; Wisconsin card sorting test; stroop test; FRONTAL-LOBE DYSFUNCTION; NEUROPSYCHOLOGICAL PERFORMANCE; COGNITIVE DEFICITS; DEPRESSION; SYMPTOMS; TESTS; CLOMIPRAMINE; SUBTYPES; OCD